ANALISIS TAMPUNGAN POTENSIAL EMBUNG BLURU UNTUK KEPERLUAN AIR BAKU KECAMATAN BATU AMPAR KABUPATEN TANAH LAUT - Afrila, Humaira; Amalia, Maya (Jurnal Teknologi Berkelanjutan, 2023)
During the dry season, Bluru Village in Tanah Laut Regency, South Kalimantan Province, has experienced water shortage frequently. Therefore, the construction of a retention basin is planned to overcome the problem. The retention basin serves to store water during the rainy season that can be used during both the wet and dry seasons. Several analyses were conducted to build a small dam. The analysis included design rainfall analysis using the Log Pearson Type III distribution, as well as design flood analysis using the Nakayasu synthetic unit hydrograph method. The flood discharge was estimated at 76.75 m3/s based on the analysis of the 100-year return period. The water demand in Bluru Village is 45.25 l/day for domestic water and 2.26 l/day for non-domestic water. The height of the Bluru Dam has a dead storage value of 231,500.00 m3 and an effective storage value of 130,000.00 m3. The dam structure was evaluated based on software simulation by Hec RAS. The dam is estimated to have a base elevation of +55.82 m and a crest elevation of +62.82 m.